Covid-19 Health Protocol Education for Health Cadres and the Community - Sudirman; Sitti Fajrah; Rikwan (Frontiers in Community Service and Empowerment, 2022)
In 2019, the government has taken policies as an effort to optimally handle the Covid-19 storm so that it does not spread widely. The pattern of transmission of the Covid-19 virus can be through the air and can be transmitted if health protocols are not carried out properly. The level of incidence of Covid-19 has become a major problem for all communities in various regions in Indonesia, including in the Parigi area of Parigi Moutong Regency. In the last week, it was discovered that a new variant of Covid-19, the "Omicron" type, has been endemic in various regions. The preliminary observations show that 75% of the public do not understand the ways and benefits of consistently implementing the Covid-19 health protocol, and 62% do not understand the risks faced if they are not disciplined with the Covid-19 health protocol. To anticipate the rate of spread of the Covid-19 virus, it is important to educate the public regarding health protocols. This activity has been carried out from June 12 to 18, 2021, using the Focus Group Discussion Method (FGD). The target is 5 health cadres and 75 people. This activity was carried out in Salabia Village, Tinombo District, Parigi Moutong Regency. This education regarding the implementation of the Covid-19 health protocol was enthusiastically welcomed by the public and health cadres. This activity is carried out to ensure that the public and health cadres are broad-minded so that they can independently implement the COVID-19 health protocol correctly with discipline and consistency.